1996
DOI: 10.1021/ma960382m
|View full text |Cite
|
Sign up to set email alerts
|

Homopolymer Interfaces Reinforced with Random Copolymers

Abstract: The strengthening of the interface between polystyrene (PS) and poly(methyl methacrylate) (PMMA) using a random copolymer P(S f -r-MMA1 - f ), where f is the fraction of styrene in the copolymer, was investigated. The maximal fracture toughness, measured by crack propagation, was found when f = 0.68. Neutron reflectivity measurements showed that this value of f corresponded to the point where the interfacial broadening on the PS and PMMA sides of the interface was symmetric. The symmetry of broadening and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 20 publications
8
102
2
1
Order By: Relevance
“…The absence of significant blockiness of styrene and 2-vinylpyridine monomers in the copolymers was verified by proton and 13 C NMR. Detailed 13 C NMR spectra are shown in the Appendix. The styrene unit in the copolymer was deuterated in order to allow for its use as a label in the subsequent FRES experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of significant blockiness of styrene and 2-vinylpyridine monomers in the copolymers was verified by proton and 13 C NMR. Detailed 13 C NMR spectra are shown in the Appendix. The styrene unit in the copolymer was deuterated in order to allow for its use as a label in the subsequent FRES experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Russell and co-workers explored PS/PMMA/P(MMA-co-S) systems and demonstrated that fracture toughness was maximized when the statistical copolymer contained 32 mole percent MMA. [23][24][25] Blend Mechanical Properties The efficacy of copolymer compatibilizers was investigated by exploring the mechanical properties of the polymer FIGURE 4 SEM images of different blends. About 100 particles were circled manually, and the number-average diameters (d n ) were determined using ImageJ software.…”
Section: Polymer Blend Compatibilizationmentioning
confidence: 99%
“…The majority of work on CLRP in the literature focuses on molecular weight control in homopolymerization, although copolymerization is of particular importance in preparing polymer products with tailored properties. [15][16][17] By changing the type of comonomers and their relative amounts, a large number of polymer products can be designed. In addition to MW and MWD, copolymer composition (CC) and copolymer composition distribution (CCD) are also key parameters that determine materials properties of a copolymer product.…”
Section: Introductionmentioning
confidence: 99%